The expansion of cattle ranching and indigenous resistance: Sertão de Amaro Leite (1822 – 1864) - Araujo, Marcilene de Assis Alves; Almeida, Maria Juliana de Freitas; Araújo, Valterlan Teixeira; Oliveira , Matheus Barbosa de; Campos , Isabella Priscilla H. (Seven Editora, 2023)
This paper presents an analysis of how the indigenous peoples of the Sertão de Amaro Leite resisted the occupation of their territories. Its purpose was to understand how this process of resistance of indigenous peoples in defense of their territories was understood as, simply, an "indigenous attack" by the settlers, as it is presented by traditional historiography. Discuss the introduction of borders as a form of appropriation and domination of the territory together with the peoples who inhabited it; get to know the indigenous peoples; understand the visions of domination and resistance when it comes to the indigenous peoples of the Sertão de Amaro Leite; relate the vision present in the period with the process of naturalization of the extermination of indigenous peoples. Regarding the methodological procedures adopted, a bibliographic review was carried out, especially the historiographic production of Goiás, and a documentary for the understanding of the problem presented. Relevant to the composition of this work were the reports of the presidents of the Province, documents that discuss the attempts of domination undertaken over the territory, as well as the resistance effected by the indigenous peoples. DOI:https://doi.org/10.56238/alookdevelopv1-118